Challenges of teaching phonics-based reading remediation in Singapore - Leung, Wai Tung (Nanyang Technological University, 2020)
Many early readers struggle to master grapheme-phoneme correspondences – the relationship between letter patterns and the speech sounds they represent in a language. There has been extensive evidence for the effectiveness of explicit systematic phonics, which teaches early readers grapheme-phoneme correspondences. In order to examine the availability and quality of evidence of school-based reading interventions for struggling early readers, a systematic review was conducted comparing phonics versus non-phonics interventions. We found limited information about group interventions targeting reading difficulties from the past decade of research. While there is more evidence supporting phonics-based reading intervention than non-phonics based, the pool of available evidence is small. We also found no bilingual studies with sufficient quality. Speakers of Singapore English are known to differ substantially in their pronunciations of vowels, compared to speakers of other varieties of English. Given the importance of grapheme-phoneme correspondences in phonics instruction, it is therefore critical to consider how differences in pronunciation of vowels in Singapore English can affect phonics instruction. In order to find out whether there are possible vowel mergers, we tested English-speaking adults with a minimal pair task in which they judged whether two words sound the same or different. We found that the adults judged word pairs differently, depending on whether the word pairs involved vowels suspected of merger. Ideally, the scope and sequence of a phonics-based instruction should begin with a small set of one-to-one letter-sound pairs that represent the most regular, highest frequency correspondences in a written language. Given the mismatches between standard scope and sequence and the regularities of the Singapore variety of English, we then discuss how this mismatch has implications for students in Singapore, and the challenges in developing a scope and sequence appropriate for Singaporean learners.